THE EFFECT OF PANORAMIC RADIOGRAPHY ON THE NUMBER OF MICRONUCLUES IN PERIODONTITIS - Khairunnisa Puspita Sari; Didit Aspriyanto; Beta Widya Oktiani (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: Periodontitis is a periodontal disease that can cause an increase in Reactive Oxygen Species (ROS). The increase in ROS concentration will cause oxidative stress which has a role in DNA damage. In the case of periodontitis, panoramic radiography plays an important role in showing generalized horizontal bone loss. Radiation on panoramic radiography may cause DNA damage. DNA damage that occurs due to periodontitis or panoramic radiographic radiation exposure is characterized by the formation of micronuclei in gingival epithelial cells. Objective: To determine the effect of panoramic radiography on the number of micronuclei in Wistar rats with periodontitis. Method: This study was true experimental with post-test only and control group design. This study used 15 male Wistar rats which divided into 5 groups. Result: The average number of micronuclei in the normal group and 1 time exposures was 4 compared to the periodontitis group without exposure was 1.67, periodontitis and 1 time exposures was 8, periodontitis and 2 times the exposure was 15.67, and in the periodontitis and 3 times the exposure was 42.67. Result of One-Way Annova test and Post Hoc Bonferroni test indicated that signigicant changes in the number of micronuclei was seen between the normal group with 1 time exposure to the periodontitis group with 2 times and 3 times exposure and int the periodontitis group without exposure to the periodontitis group with 2 times and 3 times exposure. Conclusion: Panoramic radiograph X ray radiation and periodontitis can cause changes in the number of micronuclei in wistar rats. Keywords: , Micronucleus, Panoramic Radiography, Periodontitis.